2008
DOI: 10.2319/122907-607.1
|View full text |Cite
|
Sign up to set email alerts
|

A New Premixed Self-Etch Adhesive for Bonding Orthodontic Brackets

Abstract: Objective: To determine if a new premixed self-etch adhesive can be used to successfully bond orthodontic brackets to enamel. Materials and Methods: Forty human molars were cleaned, mounted, and randomly divided into two groups. In group 1, 20 teeth were conditioned using the self-etching primer Transbond Plus (3M Unitek, Monrovia, Calif). In group 2, 20 teeth were conditioned using a new premixed selfetching adhesive, AdheSE One (Ivoclar Vivadent Inc, Amherst, NY). Both groups were bonded using brackets preco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 11 publications
2
37
0
1
Order By: Relevance
“…[181920] The bond strength of the orthodontic bracket must be able to withstand the forces applied during the orthodontic treatment. In orthodontics, an adequate bond, which fails at the enamel-composite interface, would be desirable because debonding and subsequent polishing would become much easier.…”
Section: Discussionmentioning
confidence: 99%
“…[181920] The bond strength of the orthodontic bracket must be able to withstand the forces applied during the orthodontic treatment. In orthodontics, an adequate bond, which fails at the enamel-composite interface, would be desirable because debonding and subsequent polishing would become much easier.…”
Section: Discussionmentioning
confidence: 99%
“…Einige Autoren fanden aber auch verminderte Haftwerte [5,14,26,30]. Für andere selbstätzende Primer bestehen deutlich weniger und kontroverse Daten zu deren Eignung auf unbehandelten Schmelzoberflä-chen [3,6,35,42,43].…”
Section: Introductionunclassified
“…In late 2000, a new SEP was developed particularly for orthodontic bonding. 10,11 Reports are controversial about the shear bond strengths of brackets after bleaching. Authors have generally reported that mean shear bond strength of orthodontic brackets with bleached enamel is significantly lower than that with unbleached enamel corresponding to the bleaching type or waiting period after the bleaching procedure.…”
mentioning
confidence: 99%